Ask questions, share knowledge, and connect with a vibrant community on IDNLearn.com. Ask anything and get well-informed, reliable answers from our knowledgeable community members.
Sagot :
To evaluate the expression [tex]\(2x^2 - 1\)[/tex] when [tex]\(x = 3\)[/tex], follow these steps:
1. Substitute [tex]\(x = 3\)[/tex] into the expression:
[tex]\[ 2(3)^2 - 1 \][/tex]
2. Calculate the exponent:
[tex]\[ 3^2 = 9 \][/tex]
3. Multiply by 2:
[tex]\[ 2 \cdot 9 = 18 \][/tex]
4. Subtract 1 from the result:
[tex]\[ 18 - 1 = 17 \][/tex]
So, the value of [tex]\(2x^2 - 1\)[/tex] when [tex]\(x = 3\)[/tex] is [tex]\(\boxed{17}\)[/tex]. Hence, the correct answer is:
C. 17
1. Substitute [tex]\(x = 3\)[/tex] into the expression:
[tex]\[ 2(3)^2 - 1 \][/tex]
2. Calculate the exponent:
[tex]\[ 3^2 = 9 \][/tex]
3. Multiply by 2:
[tex]\[ 2 \cdot 9 = 18 \][/tex]
4. Subtract 1 from the result:
[tex]\[ 18 - 1 = 17 \][/tex]
So, the value of [tex]\(2x^2 - 1\)[/tex] when [tex]\(x = 3\)[/tex] is [tex]\(\boxed{17}\)[/tex]. Hence, the correct answer is:
C. 17
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. Thank you for choosing IDNLearn.com for your queries. We’re committed to providing accurate answers, so visit us again soon.